A Failed New World Order and Beyond: Russian View. Issue 6 (1st November 2016) - Lukyanov, Fyodor
Abstract: Twenty-five years have passed since the Cold War, but no stable international order has been created. The idea about a Western-centric unipolar world has failed, and a multipolar system is yet to emerge, though it's hard to comment on how it may function properly. Due to its size, geopolitical location, resource potential, great power tradition and aspirations Russia finds itself in the middle of the most important trends shaping the next world order. Global demand for a stable and balanced model is intertwined with Russia's quest for its new international identity. Thus, re-assessment of the past quarter of a century is needed both internationally and nationally to pave a way to the future.